GROUND PENETRATING RADAR DATA PROCESSING USING MULTIPLE-FREQUENCY COMPOSTING TECHNIQUE WITH BERLAGE WAVELET TO DETECT UNDERGROUND PIPE MODEL WITHIN SHALLOW AREA - PRISKA (NIM: 22315013), APULINA
Mapping underground shallow infrastructures network, like mapping underground pipe network is one of geotechnic problem that needs to be solved.Ground penetrating radar (GPR) method is commonly used for this problem due to its effectivity to map objects on shallow area and its minimum effect to surrounding area, although the resolution and depth of interest of mapping really depend on the antennaÃ‚Â’s frequency. To improve the variation of size and depth of location that is going to be detected, more than one antenna frequencies are used in a measurement. For simplify the analysis of some radargrams in a same line with different frequencies, multiple-frequency composting is performed to combine those radargrams. In this research, multiple-frequency composting was performed to map some objects such as a big pipe with metal casing that surrounded with some metal cables using the results from 200 MHz dan 400 MHz antenna measurements. The composting methods used in this survey were simple summation, comparison of average radargram amplitude spectrum of each radargrams known as dominant frequency amplitude equalisation, and leastsquare weighting according to Berlage wavelet analysis known as optimal spectral whitening (OSW). Comparisons of those three methods mentioned above were performed through analysis of each radargrams and sample trace analysis on some positions to show the ability of each method in separating boundary of each medium. According to the analysis performed in this survey, multiplefrequency composting was able to improve resolution for showing underground condition, with OSW method had better ability compared to another methods.